A METHOD OF SELECTING AN UNMANNED AERIAL VEHICLE FOR THE TASK COMPLETION BASED ON A PRIOR EVALUATION OF IMAGE QUALITY - Fryz, Sergii; Myklukha, Vasyl; Avsiievych, Roman; Nechyporuk, Nataliia (Proceedings of National Aviation University (archive), 2020)
The article is devoted to the topic of current interest, namely the selection of unmanned aerial vehicle (UAV) to perform the task of a prior evaluation of image quality. The article analyzes the current condition of UAVs development and the range of tasks that are assigned to them. It is emphasized that the main task of a UAV at the present stage is aerial photography, the result of which is obtained images of the Earth‘s underlying terrain in a target area. The basic approaches to the aerial photography quality evaluation were considered. Their advantages and disadvantages were highlighted. The main quality performance criteria of photography by means of UAV were introduced, the most relevant ones were picked out for the task accomplishment. The evaluation of the aerial photography quality by using UAVs is presented as a multi-criteria decision-making task. The modern approaches to optimization of multicriteria solutions were reviewed and there was introduced an acceptable optimization model, with the help of which it became possible to automate the selection of UAV type for the assigned task. The main obtained results were analyzed and the steps of future research for solving the given tasks were developed.